The First Reference of the Effect of the Syrian Natural Zeolite on Airborne Microorganism Pollution of Broiler Farms - Berna Krikor Jilenkerian; Ali Nisafi; Ahmad Kara Ali; Bushra AI-Eissa (Recent Progress in Science and Technology Vol. 8, 2023)
The purpose of this study was to investigate the effect of three different levels of Syrian natural zeolite on the bacterial load concentrations in the air of broilers farms for six weeks. The broiler farms are considered as a reservoir of pathogenic microorganism. This research was carried out in private commercial broiler farm in the Lattakia Governorate, Syria During spring (from March to April) and autumn (from October to November) seasons. In the experiment, commercial broiler hybrid (Roos 308), with a total number (3000), were randomly assigned to four groups. This experiment was created using complete randomization, and each group (750 birds) has three replicates with 250 birds in each replicate (in addition to the control section). The findings revealed that the concentrations value for Staphylococcus spp. during spring, at the sixth week of the fattening period, in the treatment Tz3 (75%) was recorded 7.0×105, while in autumn; the value was 7.4×105 CFU/m3. And for Escherichia coli in spring, was 8.4×103 and in the autumn 8.8×103 CFU/m3. According to the findings, adding Syrian natural zeolite to broiler litter resulted in a significantly (p<0.05) lower concentration of airborne bacteria at the end of the experiment, with a superior effect to Tz3 treatment in the internal air, and the lowest concentration was observed in spring compared to autumn. This result serves as a guide for the optimal use of the various ratios of Syrian natural zeolite, as well as the development of new methods for reducing airborne microorganisms in broiler farms.